(untitled) (Research, Society and Development, 2022)
This article aims to report advances and challenges of the Extension Project “Pensa, Imagina, Inventa!” in reestablishing bonds and sharing digital health education content with a vulnerable school community in the city of Rio de Janeiro, Brazil, during the Covid-19 pandemic. It is a descriptive study, type of experience report, articulating previous knowledge and learning from remote teaching. After a period without dialogue with the community, two groups of interventions were developed: one aimed at restoring bonds and another to contribute to the health of the community, through the co-creation of different digital health education contents, prepared in a simple, attractive, and consistent with the needs identified in a community diagnosis in 2019. Despite the harm caused by the lack of face-to-face interaction for health education actions, the remote adaptation of the project was beneficial. The interventions made it possible to reconnect, disseminate useful content on health to the school community and improve technical, humanistic, and social knowledge and skills by project members, even in a context of a public health emergency.